Effective communication - Mélani Fletcher (Communicare)
In the quest to establish communication as a critical management function both literature and research have stressed the importance of effective communication as a prerequisites to the success of various programmes including service quality. Effective internal communication, leadership and employee issues seem to be three generic aspects of critical importance in the potential success of any organisation. This article will attempt to give academic insight into the link between service quality initiatives and these three aspects and will attempt to underline the importance thereof with current research results.